Enhancing acclimatization of tissue cultured plants of Albizia amara by Biotization - Indravathi, G.; Babu, P. Suresh (International Journal of Scientific Research in Biological Sciences, 2019)
The anatomical, morphological and physiological characteristics of the in vitro developed micro shoots, for a majority of the woody species, have a great impact on subsequent rooting and survival after transfer to greenhouse conditions. Any effort to improve these characteristics by controlling the stressful culture conditions undoubtedly contributes to better rooting of micro cuttings and/or acclimatization of the microplants. In the present investigation, timber yielding leguminous tree, Albizia amara has been selected for micropropagation owing to their, importance as a plant with potential medicinal value. Micropropagated plantlets usually exhibit high mortality rate upon their transfer from lab to land as a result of transplantation shock caused by abiotic and biotic stresses and weak root system. Biotization is the metabolic response of in vitro grown plant material to a microbial inoculum. It leads to morphological and physiological development of plant material thereby enhancing biotic and abiotic stress resistance. The in vitro grown micro shoots of Albizia amara with root primordia were treated with bio inoculants namely - Pseudomonas fluorescens and Trichoderma viride and transferred to plastic pots containing sterilized potting mixture (soil: peat : vermiculite: perlite in 2:1:1:1). There were four treatments viz. control, treatment with T.viride and P. fluorescens separately and dual inoculation. Percent survival of plantlets was observed maximum (82%) in dual inoculation, this must be due to the positive interaction between T.viride and P. fluorescens and their ability to enhance stress tolerance by protecting them from subsequent ‘transplantation shock’. These plantlets also exhibited an increase in root length, the number of lateral roots, shoot length, leaf number, and plant biomass.